2016
DOI: 10.1371/journal.pone.0167049
|View full text |Cite
|
Sign up to set email alerts
|

Melissa officinalis Protects against Doxorubicin-Induced Cardiotoxicity in Rats and Potentiates Its Anticancer Activity on MCF-7 Cells

Abstract: Cardiotoxicity is a limiting factor of doxorubicin (DOX)-based anticancer therapy. Due to its beneficial effects, we investigated whether standardized extract of Melissa officinalis (MO) can attenuate doxorubicin-induced cardiotoxicity and can potentiate the efficacy of DOX against human breast cancer cells. MO was administered orally to male albino rats once daily for 10 consecutive days at doses of 250, 500 and 750 mg/kg b.wt. DOX (15 mg/kg b.wt. i.p.) was administered on the 8th day. MO protected against DO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
44
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 49 publications
8
44
1
Order By: Relevance
“…Pretreatment with aqueous leaf extract showed increased level of total antioxidant status confirming the antioxidant activity of Murraya leaf extract. Results of this present study were in harmony with previous studies done by Al-Harthi et al and Hamza et al [51,55]. e superoxide anions and their derivatives specially the highly reactive and damaging hydroxyl radicals formed in doxorubicin metabolism cause the lipid peroxidation of the cell membrane [51].…”
Section: Evidence-based Complementary and Alternative Medicinesupporting
confidence: 92%
See 2 more Smart Citations
“…Pretreatment with aqueous leaf extract showed increased level of total antioxidant status confirming the antioxidant activity of Murraya leaf extract. Results of this present study were in harmony with previous studies done by Al-Harthi et al and Hamza et al [51,55]. e superoxide anions and their derivatives specially the highly reactive and damaging hydroxyl radicals formed in doxorubicin metabolism cause the lipid peroxidation of the cell membrane [51].…”
Section: Evidence-based Complementary and Alternative Medicinesupporting
confidence: 92%
“…leaf extract significantly reduced the lipid peroxidation suggesting the antioxidant potential of the plant. Many previous studies on natural products or other compounds with high amount of antioxidants have shown a reduction of lipid peroxidation in doxorubicin-induced cardiotoxicity [27,51,52,54,55].…”
Section: Evidence-based Complementary and Alternative Medicinementioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms of doxorubicin‐associated cardiac toxicity are not fully elucidated; however, cardiac cell apoptosis by ROS is a known side effect of doxorubicin. Multiple reports have demonstrated that doxorubicin‐induced cardiac toxicity is decreased by anti‐apoptotic methods in various animal models . It is known that ursolic acid protects the heart from ischaemic reperfusion injury or infarction by anti‐apoptotic activities .…”
Section: Discussionmentioning
confidence: 99%
“…The supernatant sample was used for estimating antioxidant enzymes markers. The total protein content was measured by the technique designed by Taylor et al The catalase (CAT) action was evaluated by Liu et al method . The superoxide dismutase (SOD) action was assessed by Mayer et al method .…”
Section: Methodsmentioning
confidence: 99%